The Influence of Self-Efficacy and Emotional Intelligence on Employee Work Productivity - Adam Ramadhan; Agus Halim (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study examines the partial and simultaneous effects of self-efficacy and emotional intelligence on employee work productivity at PT. Suraco Jaya Abadi Motor Mamuju. It hypothesizes that both psychological factors positively and significantly influence employee productivity. Research Method: A quantitative causal-associative design was employed. The study involved all 34 permanent employees selected through census sampling. Data were collected using a structured five-point Likert-scale questionnaire and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, an F-test, and the coefficient of determination with SPSS. Results and Discussion: Self-efficacy positively and significantly affected work productivity (β = 0.425; t = 3.842; p = 0.001). Emotional intelligence also had a positive and significant effect (β = 0.388; t = 3.115; p = 0.004). Simultaneously, both variables significantly influenced employee productivity (F = 24.615; p < 0.001). These findings demonstrate that confidence in completing work tasks and the ability to manage emotions strengthen employee effectiveness and productivity. Implications: Management should provide self-development, coaching, emotional management, and interpersonal communication programs. Future studies should examine broader samples and additional determinants of productivity. Originality: This study integrates self-efficacy and emotional intelligence in explaining employee productivity within an automotive dealership context in West Sulawesi.